Vitamin D Levels and Early Onset Sepsis in Newborns. Issue 2 (June 2021) - Jeengar, Balveer; Gothwal, Sunil; Meena, Kailash Kumar; Garg, Vijendra Kumar; Athwani, Vivek; Gupta, Manohar Lal; Meena, Kuldeep; Bairwa, Ghan Shyam
Aim: To find out association between vitamin D level and early onset neonatal sepsis (EONS). Methods: This case control study was conducted at a tertiary care center in Northern India during June 2018 to May 2019. Neonates with culture-proven EONS were included as case and neonates without EONS were enrolled as control. 25OH-D levels were evaluated with other routine blood samples. Statistical analysis was done by using unpaired t test and chi-square test. Results: Sixty-two infants were enrolled in each group; baseline characteristics were comparable in both groups. Risk of EONS increased 8 times in neonates with 25OH-D level <30 ng/mL (odds ratio = 8.2; 95% confidence interval [CI]: 3.08-21.82; P = .000). The 25OH-D level was significantly lower in EONS group than control group. Optimal cut-off for 25OH-D was 25 ng/mL to predict EONS with a sensitivity and specificity of 88.7% and 79%, respectively (area under the curve: 0.84; 95% CI: 0.76-0.92; P = .000). Conclusions: Vitamin D insufficiency is significantly associated with EONS. Vitamin D deficiency significantly increases risk of EONS. Maternal vitamin D supplementation may improve neonatal vitamin D levels and may decreases risk of EONS. Further studies including maternal vitamin D level are required for implementation.